Changes in physical activity across a 6‐month weight loss intervention in adolescents with intellectual and developmental disabilities. Issue 6 (16th December 2021) - Ptomey, L. T.; Lee, J.; White, D. A.; Helsel, B. C.; Washburn, R. A.; Donnelly, J. E.
Abstract: Background: Adolescents and young adults with intellectual and developmental disabilities (IDD) have high rates of obesity and low levels of physical activity. This analysis examined changes in light, moderate‐to‐vigorous physical activity (MVPA) and sedentary time, and the association between changes in MVPA and weight loss in adolescents and young adults with IDD and overweight and obesity participating in a 6‐month multi‐component weight loss intervention. Methods: Adolescents and young adults with IDD and overweight or obesity (body mass index ≥ 85 percentile, n = 110, age 16 years, 52.7% female) and a parent were randomised to one of three intervention groups: face‐to‐face delivery/conventional reduced energy diet ( n = 36), remote delivery (RD)/conventional reduced energy diet ( n = 39), or RD/reduced energy enhanced stop light diet (eSLD) ( n = 35.) Participants were asked to engage in 60 min/day of MVPA on 5 or more days/wk. Participants and a parent attended twice monthly education/behavioural counselling sessions with a health educator to assist participants in complying with dietary and MVPA recommendations. Education/counselling in the RD arms was delivered remotely using video conferencing, and self‐monitoring of MVPA and daily steps was completed using a wireless activity tracker. Education/counselling in the face‐to‐face arm was delivered during home‐visits and self‐monitoring of MVPA and daily steps was completed by self‐report using paper tracking forms designed for individuals with IDD. MVPA, light activity, and sedentary time were assessed over 7 days at baseline and 6 months using a portable accelerometer (ActiGraph wGT3x‐BT). Results: Mixed modelling analysis completed using participants with valid accelerometer data (i.e. ≥4–10 h days) at baseline ( n = 68) and 6 months ( n = 30) revealed no significant changes in light, moderate‐ MVPA, or sedentary time across the 6‐month intervention (all P > 0.05). Participants obtained 15.2 ± 21.5 min/day of MVPA at baseline and 19.7 ± 19.7 min/day at 6 months ( P = 0.119). Mixed modelling indicated no significant effects of group ( P = 0.79), time ( P = 0.10), or group‐by‐time interaction ( P = 0.21) on changes in MVPA from baseline to 6 months. Correlational analysis conducted on participants with valid accelerometer data at both baseline and 6 months ( n = 24) revealed no significant associations between baseline sedentary time ( r = 0.10, P = 0.40) and baseline MVPA ( r = −0.22, P = 0.30) and change in MVPA across the 6‐month intervention. Additionally, attendance at education/counselling sessions ( r = 0.26, P = 0.22) and frequency of self‐monitoring of MVPA were not significantly associated with change in MVPA from baseline to 6 months ( r = 0.26, P = 0.44). Baseline MVPA ( r = 0.02, P = 0.92) and change in MVPA from baseline to 6 months ( r = 0.13, P = 0.30) were not associated with changes in body weight across the 6‐month intervention. Conclusion: We observed a non‐significant increase in MVPA (30%), which was not associated with the magnitude of weight loss in a sample of adolescents and young adults with IDD who participated in a 6‐month multi‐component weight loss intervention. Additional strategies to increase MVPA in adolescents and young adults with IDD participating in weight loss interventions need to be developed and evaluated.